2022
DOI: 10.1126/sciadv.add3868
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturizing color-sensitive photodetectors via hybrid nanoantennas toward submicrometer dimensions

Abstract: Digital camera sensors use color filters on photodiodes to achieve color selectivity. As the color filters and photosensitive silicon layers are separate elements, these sensors suffer from optical cross-talk, which sets limits to the minimum pixel size. Here, we report hybrid silicon-aluminum nanostructures in the extreme limit of zero distance between color filters and sensors. This design could essentially achieve submicrometer pixel dimensions and minimize the optical cross-talk arising from tilt illuminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…[98] Ho et al demonstrated a hybrid Si-Al nanostructure-based Schottky detector, for visible color-selective detection due to the Mieplasmon resonance of magnetic dipole supported in such hybrid nanoantennas. [99] By utilizing such concept, there might also have a strong possibility on III-V semiconductor nanowire arraybased Schottky photodetectors to further extend the detection range and improve the performance.…”
Section: Schottky Junction Photodetectorsmentioning
confidence: 99%
“…[98] Ho et al demonstrated a hybrid Si-Al nanostructure-based Schottky detector, for visible color-selective detection due to the Mieplasmon resonance of magnetic dipole supported in such hybrid nanoantennas. [99] By utilizing such concept, there might also have a strong possibility on III-V semiconductor nanowire arraybased Schottky photodetectors to further extend the detection range and improve the performance.…”
Section: Schottky Junction Photodetectorsmentioning
confidence: 99%
“…Previous efforts often focused on metallic metasurfaces [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], which can enhance light–matter interactions and introduce versatile control of incoming light by activating local plasmonic resonance, albeit with limited efficiency due to ohmic loss [ 78 , 79 , 80 , 81 , 82 , 83 ]. Dielectric metasurfaces overcome the limitation of metallic metasurfaces, which have provided a promising way to develop highly efficient and multi-functional meta-devices [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption of light and the conversion of photons into other forms of energy, such as excitons and phonons, have been widely utilized for optical sensing, , imaging, and energy harvesting . Recently, rapid developments in wearable devices and emergence of the Internet of Things have further increased the demand for smaller photodetectors (PDs) with high absorption efficiency. , Compact integrated PDs could potentially provide several advantages for these applications, including high-resolution imaging thanks to the large pixel count, , reduced energy consumption, and high-speed operation . However, two major limitations impede their functionalities: a small device footprint limits the total light collection, and a small device thickness limits the total amount of absorbed light (Figure a).…”
mentioning
confidence: 99%
“…In addition, the responsivity of this single-junction meta-optical PD depends on the wavelength and polarization of light, which can be further exploited to create a spectrally selective and polarization-sensitive miniaturized PD. Such multifunctionality can reduce the fabrication costs and optical crosstalk between pixels and have far-reaching impact on wearable sensors, including miniature spectrometers and Li-Fi transducers. …”
mentioning
confidence: 99%
See 1 more Smart Citation